Manajemen Strategi Pesantren Dalam Pendidikan Berbasis Transformasi Budaya Dan Politik (Sophist: Jurnal Sosial Politik Kajian Islam dan Tafsir, 2021)
Education is one element that plays a very strategic role in the development of a family, community, and nation. The progress and retreat of a nation can be seen from the development and quality of education. The more focused the implementation of education will lead a nation to a more advanced civilization. Every educational institution, both large and small educational institutions, must have various goals to be achieved, and these goals require a regulatory process through management. Islamic boarding schools as places of education and teaching consisting of several groups of people such as kyai or master teachers as leaders or caregivers, boarding school administrators, and students are a unit involved in carrying out educational activities. The presence of madrasas / Islamic boarding schools and other institutions in carrying out transformation-based education in the boarding school environment as an effort to continue the development of science and knowledge and technology certainly requires management or management which will eventually become an educational system of Islamic boarding school education, because management is basically contains three meanings. First, management as a process, second, management as a collectivity of people who carry out management activities, third, management as an art and science.
Keywords: Management; pesantren; education; culture and politics